Identification of allelic variants implicated in neonatal encephalopathy with suspected hypoxic ischaemic encephalopathy and consequential cerebral palsy in individuals of African origin - Pepper, Michael Sean (University of Pretoria, 2025)
Dissertation (MSc (Medical Immunology))--University of Pretoria, 2025.